New advances on Silurian conodont biostratigraphy in the Central Precordillera, Argentina - Heredia, Susana (2010)
Recent studies on classical Silurian sections of the Central Precordillera provided conodont faunas which allow the proposal of a new biostratigraphical chart for the Silurian deposits of the Precordillera. The Cerro del Fuerte, Loma de Los Piojos, Cerro La Chilca and Pachaco sections were sampled for conodonts. The conodont faunas allowed us to identify the Kockelella variabilis variabilis Zone (middle Gorstian), the Ancoradella ploeckensis Zone (upper Gorstian ? lower Ludfordian), and the Zieglerodina? zellmeri or the base of the Ozarkodina eosteinhornensis Zone (lower Pridolì). The A. ploeckensis Zone is mentioned in the Precordillera for the first time. This index conodont would question whether K. variabilis variabilis Walliser is the guide conodont for Los Espejos Formation in the eastern outcrops or just a species in the association of the A. ploeckensis Zone.